Identification of Extracellular Carbonic Anhydrase of Chlamydomonas reinhardtii - Coleman, John R. (1984)
We have examined the induction of carbonic anhydrase activity in Chlamydomonas reinhardtii and have identified the polypeptide responsible for this activity. This polypeptide was not synthesized when the alga was grown photoautotrophically on 5% CO(2), but its synthesis was induced under low concentrations of CO(2) (air levels of CO(2)). In CW-15, a mutant of C. reinhardtii which lacks a cell wall, between 80 and 90% of the carbonic anhydrase activity of air-adapted cells was present in the growth medium. Furthermore, between 80 and 90% of the carbonic anhydrase is released if wild type cells are treated with autolysin, a hydrolytic enzyme responsible for cell wall degradation during mating of C. reinhardtii. These data extend the work of Kimpel, Togasaki, Miyachi (1983 Plant Cell Physiol 24: 255-259) and indicate that the bulk of the carbonic anhydrase is located either in the periplasmic space or is loosely bound to the algal cell wall. The polypeptide associated with carbonic anhydrase activity has a molecular weight of approximately 37,000. Several lines of evidence indicate that this polypeptide is responsible for carbonic anhydrase activity: (a) it appears following the transfer of C. reinhardtii from growth on 5% CO(2) to growth on air levels of CO(2), (b) it is located in the periplasmic space or associated with the cell wall, like the bulk of the carbonic anhydrase activity, (c) it binds dansylamide, an inhibitor of the enzyme which fluoresces upon illumination with ultraviolet light, (d) antibodies which inhibit carbonic anhydrase activity only cross-react with this 37,000 dalton species.